Form and properties of the canonical Weierstrass product of an entire function with real values on $\mathbb{R}$ - Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.2 We determine the form and properties of the Weierstrass canonical product of an entire function with real values on $\mathbb{R}$. The proof of the theorem on the order of $R$-integral is specified [${\it Samoilenko\, A. M.}$ Order and canonical product of the Weierstrass $R$-integral // Ukr. Mat. Zh. — 2019. — ${\bf 71}$, № 4. — P.564-570].